The Effect of Transformational Leadership on Job Satisfaction Mediated by Organizational Citizenship Behavior (OCB) - Tran Sida Yulia Ningsih; sandra irawati; iqbal ramadhani fuadiputra (Jamanika (Jurnal Manajemen Bisnis dan Kewirausahaan), 2023)
This study aims to determine how transformational leadership influences employee performance, and whether OCB variables can mediate the relationship between transformational leadership style and employee performance. This research was conducted on employees of the General Sector of the Probolinggo Regency Food Security and Agriculture Service with a total of 30 respondents. The sampling technique in this study used saturated sampling where all populations were sampled. Data collection in this study used a questionnaire which was analyzed with a scale range and Partial Least Square (PLS) 4.0. The results of calculating this scale range show that transformational leadership is at a high level, employee performance is in the high category, and Organizational Citizenship Behavior is in the strong category. The results of this study indicate that transformational leadership has a positive and significant effect on employee performance. Transformational leadership has a positive and significant effect OCB. Organizational citizenship behavior (OCB) has a positive and significant effect on employee performance and is able to mediate the effect of the relationship between transformational leadership on employee performance.